THE CONTINUITY OF PEASANT AGRICULTURE IN THE CITY OF MARMELEIRO (PR) - Braga, Luis Carlos [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, 2019)
The main aim of this study is to identify and understand the persistence of the peasantry in agriculture in the municipality of Quince - located in the southwestern of Parana - following implantation from continuing expansion of the so-called modernization in agriculture. In this regard, it was identified various difference of rates of working pattern upon agricultural production, both slow and fast, by means of concepts of time and territory, and the notion of territoriality and temporality. Thus, the rhythms of time will be shown, highlighting the permanence of the main variables. Therefore, in order to verify that the production of poultry and tobacco was examined under an integration system; in grain production (soybean and corn); overall milk production and production for human consumption, thus demonstrating how these activities interfere the rhythm of the small farmers, coexisting side by side with peasant elements which are still present and important inside the studied city.
Keywords: Mechanization; Peasants elements; Temporality